Determining Diseases in Goldfish Using WEB-Based Forward Chaining Expert System Technology in Lawe Malum Village - paisalpaisal; Supina Batubara; Rio Septian Hardinata (Yayasan Sinergi Multidimensi Kreatif, 2024)
Type lots of fish cultivated by farmer fish is Goldfish caused​ because convenience in cultivated and marketed Because many can​ utilized from Goldfish . That problem often happen is farmer goldfish are not in a way routine do maintenance cause fish caught disease . Case the caused because farmer Still lay to symptom and type disease in cultivation goldfish , so make easy goldfish​ attacked disease . This matter make farmer difficulty in handling to disease that arises exercise symptom Because limited knowledge . Limitations expert in field knowledge cultivation fish sir is Wrong One frequent problem​ found in various area . Study This aim For identification disease on goldfish use​ technology system Forward Chaining expert based symptoms And designing System Expert in identify disease And method treatment on goldfish . Necessary data moment study This is data type symptom And type disease based on symptom on goldfish , symptom data and treatment data take sourced decisions​ from expert cultivation goldfish from​ a school teacher Intermediate Vocational major cultivation fishery and the data obtained from Service Municipal Fisheries . Based on the data provided by expert , expert own method taking decision , that is gather facts moreover formerly For reach something conclusion or decision , so technology system expert can used For do study This . Stages processing the data like prepare data input, tables decision experts , determine rules, carry out tracking processes , create decision tree And results tracking . The results obtained succeed find disease based on existing symptoms​ And can found as well as solution step beginning For handling to disease goldfish . Results test try doing that with compare data with system that has designed own level very accuracy​ Good .